2019
DOI: 10.1177/1403494818817411
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying and traditional bullying among Nordic adolescents and their impact on life satisfaction

Abstract: Aims: The aim of this study was to investigate the prevalence of cybervictimization in the six Nordic countries and to assess its overlap with traditional bullying. A further aim was to examine potential associations between life satisfaction, on the one hand, and traditional bullying and cyberbullying on the other. Methods: Analyses were based on data from the 2013⁄2014 Health Behaviour in School-aged Children study. It included 32,210 boys and girls, aged 11, 13, and 15, living in the six Nordic cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 34 publications
6
34
2
3
Order By: Relevance
“…Smith et al (26) found that traditional bully victims were more likely to seek help than cyberbully victims, and Dooley et al (27) found that being a cyberbully victim was not related to help-seeking in two samples of adolescents. A cross-national study among adolescents aged 11, 13, and 15 years from the Nordic countries (N = 32,210) showed that being exposed to cyberbullying was linked to lower life satisfaction (28). Cyberbully victimization has also been found to be related to worse mental health outcomes for adolescents generally, but especially for girls (18,29), indicating the need for victims to receive help.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al (26) found that traditional bully victims were more likely to seek help than cyberbully victims, and Dooley et al (27) found that being a cyberbully victim was not related to help-seeking in two samples of adolescents. A cross-national study among adolescents aged 11, 13, and 15 years from the Nordic countries (N = 32,210) showed that being exposed to cyberbullying was linked to lower life satisfaction (28). Cyberbully victimization has also been found to be related to worse mental health outcomes for adolescents generally, but especially for girls (18,29), indicating the need for victims to receive help.…”
Section: Discussionmentioning
confidence: 99%
“…Smith, Mahdavi, Carvalho, Fisher, Russell and Tippett (2008, p. 376) defines cyberbullying as “An aggressive, intentional act carried out by a group or individual, using electronic forms of contact, repeatedly and over time against a victim who cannot easily defend him or herself.” Prevalence rates of cyberbullying vary a lot from for example 4.8% to 73.5% with a median of 23.0% as found in a review by Hamm, Newton, Chisholm, Shulhan, Milne, Sundar and Hartling (2015). Arnarsson, Nygren, Nyholm, Torsheim, Augustine, Bjereld and Bendtsen (2019) found even lower prevalence rates, which may partly be explained by the use of different measures to assess cyberbullying. The prevalence of being cyberbullied, bullied in a traditional manner, or both was 1.6%, 2.7%, and 1.6%, respectively, for 15‐year‐old Norwegian boys and 2.6%, 3.1%, and 1.9% for 15‐year‐old Norwegian girls (Arnarsson et al ., 2019).…”
Section: Cyberbullying Status and Mental Health In Norwegian Adolescentsmentioning
confidence: 99%
“…Arnarsson, Nygren, Nyholm, Torsheim, Augustine, Bjereld and Bendtsen (2019) found even lower prevalence rates, which may partly be explained by the use of different measures to assess cyberbullying. The prevalence of being cyberbullied, bullied in a traditional manner, or both was 1.6%, 2.7%, and 1.6%, respectively, for 15‐year‐old Norwegian boys and 2.6%, 3.1%, and 1.9% for 15‐year‐old Norwegian girls (Arnarsson et al ., 2019). These rates indicate that the overlap between traditional bullying and cyberbullying is relatively low in Norway (Arnarsson et al ., 2019).…”
Section: Cyberbullying Status and Mental Health In Norwegian Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of bullying in relation to perceived life satisfaction has only recently begun to be addressed. Available results show that bullying tends to have a negative impact on subjective adolescent well-being: lower levels of life satisfaction tends to be observed in adolescents who have suffered cyberbullying as opposed to those who have not been bullied (Arnarsson et al, 2019), as well as lower average levels of well-being in preadolescent bullying victims, with victimization being the variable posing the greatest negative impact to well-being (Alcántara et al, 2019). Similarly, Savahl et al (2018) show the negative relationship between subjective well-being and bullying in preadolescents from different countries.…”
Section: Introductionmentioning
confidence: 99%